(untitled) (Research, Society and Development, 2024)
The literature defines Temporomandibular Disorder (TMD) as a set of disorders that affect the masticatory muscles, the temporomandibular joint and associated structures. When properly diagnosed, most patients with TMD respond favorably to conservative, reversible and affordable treatment. Botulinum toxin is a non-invasive procedure, with quick results, compared to invasive treatments, has a safe composition, has good prognoses and has a scientific basis when used in the dental area as a functional and aesthetic treatment, especially in the area of TMD. Thus, the objective of this study was to identify, through scientific publications, the application of botulinum toxin in the treatment of temporomandibular disorders. This is a literature review. The search took place from September 26th to November 6th, 2023, in the databases: PubMed and Scielo. According to the articles that supported this study, TMD is multifactorial and has received attention from different health professionals, such as orthopedists, neurologists, psychiatrists, otorhinolaryngologists, psychologists and physiotherapists. It was considered that the application of botulinum toxin type A to the muscles associated with MRD aims to temporarily reduce local muscle activity, inhibiting the release of the neurotransmitter acetylcholine at the neuromuscular junction, providing relief and comfort to the patient.